Le musiche d'arte del XXI secolo in prospettiva storica atti della seconda giornata di studio, 9 novembre 2021. - Bizzarini, Marco (Chiavi musicali, 2022)
The second volume of the "Musical Clefs" series continues the reflections started in the previous issue dedicated to 21st century art music in historical perspective. It discusses topics such as the impact of social media on musical genres, the current historiography of music, the relationship between film music and the digital universe, contemporary listening, the excesses of our epoch, the new output of string quartet in Italy, Schoenberg's ideological legacy, recent works by Francesco Filidei, Luigi Esposito and Dario Buccino. Dedicated to the memory of the musicologist Antonio Rostagno, this publication presents essays by Emanuele D'Onofrio, Tiziana Pangrazi, Roberto Calabretto, Maria Rossetti, Luigi D'Istria, Francesco Filidei, Luigi Esposito, Pietro Misuraca, Marica Coppola, Enrico Careri. The index of names also includes references to the previous book.